2010
DOI: 10.1002/jrs.2588
|View full text |Cite
|
Sign up to set email alerts
|

Raman studies on nanocomposite silicon carbonitride thin film deposited by r.f. magnetron sputtering at different substrate temperatures

Abstract: Raman studies of nanocomposite SiCN thin film by sputtering showed that with increase of substrate temperature from room temperature to 500

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 31 publications
(58 reference statements)
2
22
0
Order By: Relevance
“…Bhattacharyya and coworkers used Raman scattering to study nanocomposite SiCN thin films prepared by sputtering and showed that as the substrate temperature increased from room temperature to 500°C, a transition from mostly sp 2 graphitic phase to sp 3 carbon took place . A combined theoretical and experimental Raman study was presented by Fazze et al .…”
Section: Solid‐state Studiesmentioning
confidence: 87%
See 1 more Smart Citation
“…Bhattacharyya and coworkers used Raman scattering to study nanocomposite SiCN thin films prepared by sputtering and showed that as the substrate temperature increased from room temperature to 500°C, a transition from mostly sp 2 graphitic phase to sp 3 carbon took place . A combined theoretical and experimental Raman study was presented by Fazze et al .…”
Section: Solid‐state Studiesmentioning
confidence: 87%
“…[199] showed that as the substrate temperature increased from room temperature to 500 C, a transition from mostly sp 2 graphitic phase to sp 3 carbon took place. [202] A combined theoretical and experimental Raman study was presented by Fazze et al on a di-Ph bithiophene molecule known as a good candidate for the development of organic nonvolatile memory devices. [203] These results open the way for the identification of the molecular isomers present in the thin film of a memory cell and also of the active molecular species involved in the switching mechanism of the operating device.…”
Section: Glasses Ceramics and Disordered Materialsmentioning
confidence: 99%
“…36,38,41,42 Since the N atom is trivalent and the silicon atom is tetravalent, H content in the film has minimal effect on the mobility of films: conformality is difficult to achieve and reflow is not observed in post-deposition process windows. 34,85,91 In contrast, the lower dissociation energies associated with NH 3 and SiI 4 allows deposition at lower temperatures. 105,106 Additionally, chemical pathways associated with silicon diimide and diiodosilylene formation from SiI 4 are enabled for deposition.…”
Section: Overview Of Silicon Nitride Source Chemistriesmentioning
confidence: 99%
“…ALD SiN x work 86,87,100,117 was carried out in three different modes: thermal (no plasma), PA-ALD (where the plasma was generated in the reactor directly above the substrate), and PE-ALD (where the plasma was generated remotely and transported into the reactor). For thermal ALD, the majority of the work focused on the reaction of halosilanes and N-bearing reactants, including: (a) SiI 4 and NH 3 • C. 117 Only two of the reports 87,117 presented compositional analysis results for the SiN x films. The findings indicated that lower deposition temperatures produced substoichiometric films that oxidized upon exposure to air.…”
Section: Atomic Layer Deposition (Ald)mentioning
confidence: 99%
See 1 more Smart Citation